2016
DOI: 10.1080/19942060.2016.1157099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the piston top contour on the tumble flow and combustion features of a GDI engine with a CMCV: a CFD study

Abstract: In spite of much progress in the development of gasoline direct injection (GDI) engines, choosing an appropriate piston top contour to obtain desirable combustion efficiency is still an arduous process for engineers. This study investigates the combined effects of piston bowl geometry and a charge motion control valve (CMCV) on tumble flow and combustion features in GDI engines. Based on the model validation, the processes of intake, spray, mixture formation and combustion at different engine speeds are simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…As previously highlighted, PumpLinx adopts the k-ε model, which is widely used in the prediction of several turbulent flow calculations due to its robustness, economy, and reasonable accuracy for a wide range of flows. However, it has been also demonstrated that this model performs poorly when faced with non-equilibrium boundary layers as in the case of -tumble‖ motion at the entrance [50].…”
Section: Scroll Simulation Without Axial Gapmentioning
confidence: 99%
“…As previously highlighted, PumpLinx adopts the k-ε model, which is widely used in the prediction of several turbulent flow calculations due to its robustness, economy, and reasonable accuracy for a wide range of flows. However, it has been also demonstrated that this model performs poorly when faced with non-equilibrium boundary layers as in the case of -tumble‖ motion at the entrance [50].…”
Section: Scroll Simulation Without Axial Gapmentioning
confidence: 99%
“…Such simplifying assumptions, even if may affect the consistency of the heat transfer estimation at a local level, should not drastically influence the accuracy of the prediction the in-cylinder flow and turbulence fields, which are the main focuses of the presented work. A similar approach was followed in other researches oriented to the flow description, such as, for instance, [11,12].…”
Section: Cfd 3d Model Setup and Preliminary Validationmentioning
confidence: 99%
“…The cylinder-to-cylinder variation is closely associated with the intake process in GDI engines, and it is inevitable, but it has a crucial impact on engine performance 16 . Additionally, in the GDI engine system, the tumble flow in the cylinder generated by intake process determine the turbulent intensity, mixing process, and further the combustion process 17 . Therefore, the intake system needs to be developed because the difference of charged air mass and turbulent intensity by intake manifold geometry between cylinders causes the variation of combustion characteristics 18 .…”
Section: Introductionmentioning
confidence: 99%